The how's and why's of obesity - Bortz, Walter M.; American College of Sports Medicine; Monterey Bay Video Production Co.; Insight Media ([Indianapolis, In.] : Monterey Bay Video Production Co. [production] ; New York : Insight Media [distributor], 2004)
Presents an overview of the cultural background factors underlying this epicdemic, and provides basic information and insights that can help resolve the problem and lead to a sensible and realistic solutions
Title from title screen
Keywords: Obesity; Exercise